2019
DOI: 10.1186/s13075-019-1975-y
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical and clinical atherosclerosis in rheumatoid arthritis: results from the 3-year, multicentre, prospective, observational GIRRCS (Gruppo Italiano di Ricerca in Reumatologia Clinica e Sperimentale) study

Abstract: Background: Rheumatoid arthritis (RA) is associated with an increased risk of morbidity and mortality, when compared with general population, largely due to enhanced atherosclerotic disease. In this work, we aimed at assessing both occurrence and predictive factors of subclinical and clinical atherosclerosis in RA. Methods: From January 1, 2015, to December 31, 2015, consecutive participants with RA, admitted to Italian Rheumatology Units, were assessed in the GIRRCS (Gruppo Italiano di Ricerca in Reumatologia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 63 publications
0
40
0
1
Order By: Relevance
“…The country of publication differed between the included studies. There were six studies conducted among RA patients in North America (the USA) [ 16 , 19 , 33 , 34 , 37 , 40 ], two studies in Latin America (Mexico, Colombia, and Brazil) [ 12 , 14 ], two in Asia Pacific (Australia and Taiwan) [ 25 , 35 ] and six in Europe (France, Sweden and Netherlands) [ 11 , 15 , 17 , 36 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The country of publication differed between the included studies. There were six studies conducted among RA patients in North America (the USA) [ 16 , 19 , 33 , 34 , 37 , 40 ], two studies in Latin America (Mexico, Colombia, and Brazil) [ 12 , 14 ], two in Asia Pacific (Australia and Taiwan) [ 25 , 35 ] and six in Europe (France, Sweden and Netherlands) [ 11 , 15 , 17 , 36 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, no standard criteria were used when selecting the RA patients [ 37 ], ascertaining exposure to MTX [ 15 , 39 ], or the occurrence of T2D [ 17 , 25 , 37 , 38 , 40 ]. Five studies recruited RA patients with incident T2D [ 16 , 19 , 34 , 37 , 40 ] while other studies included RA patients with prevalent T2D [ 11 , 12 , 14 , 15 , 17 , 25 , 33 , 35 , 36 , 38 , 39 ]. All included studies reported the use of DMARDs and provided details of the drug names except one study [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Литературные данные также демонстрируют факт кумуляции структурных сосудистых нарушений у больных РА с метаболическим синдромом [12]. Вместе с тем в недавнем проспективном исследовании показано, что наибольший прирост частоты субклинического и клинического атеросклероза был зафиксирован в первые 5 лет РА [13]. Эти особенности требуют более внимательного подхода к выявлению и модификации факторов риска ССЗ, а также диагностике и раннему лечению атеросклероза у больных с началом РА после 45 лет, особенно в дебюте заболевания.…”
Section: Discussionunclassified
“…Skeoch et al demonstrated in their study the increased prevalence of atherosclerosis in RA, providing data to confirm that atheroma plaques are at high risk of complications [38]. Ruscitti et al have shown increased incidence and prevalence of subclinical and clinical atherosclerosis in RA patients, but reaching and maintaining remission had positive effect on the atherogenesis development [39].…”
Section: Macrovascular Involvement In Ramentioning
confidence: 92%